2011
DOI: 10.1007/s11745-010-3511-3
|View full text |Cite
|
Sign up to set email alerts
|

Low Levels of the Omega‐3 Index are Associated with Sudden Cardiac Arrest and Remain Stable in Survivors in the Subacute Phase

Abstract: In previous studies, low blood levels of n-3 fatty acids (FA) have been associated with increased risk of cardiac death, and the omega-3 index (red blood cell (RBC) eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) expressed as weight percentage of total FA) has recently been proposed as a new risk factor for death from coronary artery disease, especially following sudden cardiac arrest (SCA). As blood samples often haven been harvested after the event, the aim of our study was to evaluate the stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 27 publications
3
34
0
3
Order By: Relevance
“…An epidemiologic study reported that the risk of SCD was lower in individuals with long-term fi sh consumption ( 31 ). This fi nding is consistent with studies reporting that a low omega-3 index increased the risk of ventricular fi brillation during acute ischemic phase of a MI and SCD ( 32,33 ).…”
Section: Downloaded Fromsupporting
confidence: 72%
“…An epidemiologic study reported that the risk of SCD was lower in individuals with long-term fi sh consumption ( 31 ). This fi nding is consistent with studies reporting that a low omega-3 index increased the risk of ventricular fi brillation during acute ischemic phase of a MI and SCD ( 32,33 ).…”
Section: Downloaded Fromsupporting
confidence: 72%
“…From these values we derived the omega-3 index (RBC EPA and DHA expressed as weight percentage of total fatty acids). 21 In our study population, on average DHA consisted of 87.4% of the sum DHAϩEPA. The interassay coefficient of variation was 4.9% for both EPA and DHA.…”
mentioning
confidence: 77%
“…Since the Omega-3-Index is inversely [35], and AA/EPA ratio directly associated with CVD risk [36], the results indicate additional aronia-juice cardio-protective effects.…”
Section: Discussionmentioning
confidence: 86%